CHANGING PATTERNS OF MIGRATION IN HARYANA - Rahul (International Journal of Research -GRANTHAALAYAH, 2022)
The freedom of movement and freedom to settle down in India are enshrined in clauses (d) and (e) of Article 19 (1) of the Constitution. Haryana has experienced a transformation in its economic sectors: from agrarian to industrial and service oriented. However, studying the changing migration pattern in the economically developed Haryana state has become essential. This study, mainly based on the last three rounds of the Indian Census, is an attempt to study the situation of migration. The study revealed an increase in the absolute number of total migrants on the one hand and a decline in the rate of migration on the other. In the state, migrants moving within a district have recorded the highest annual migration rate from 2001 to 2011, indicating that migration is becoming a short-distance phenomenon. Further, the migration rate was seen to be higher among the migrants from one urban area to another, both among intrastate and interstate migrants. Economic and demographic factors such as per capita income and urbanization have been found to be strongly related to interstate in-migration.